1988
DOI: 10.1161/01.str.19.2.196
|View full text |Cite
|
Sign up to set email alerts
|

Amaurosis fugax in a Danish community: a prospective study.

Abstract: A prospective study of amaurosis fugax was carried out in a Danish community (population 481,000); case ascertainment was based on the collaboration of practicing ophthalmologists and general practitioners. Over a 3-year period we registered 131 cases; the annual incidence of "first amaurosis fugax episodes coming to medical attention" was 8.6 and 6.2 per 100,000 population for men and women, respectively. On the basis of a comparison of the age-incidence curves for cerebral and retinal ischemic attacks, the "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…The percentage of carotid cases is considerably higher than that reported in Japan 8,14 but is similar to that reported in Oxfordshire. 5 The incidence of TMB in the present study is higher than that reported in a prospective study from Denmark, 16 but the frequency of TMB among all TIA cases (19%) is similar (17%) to that reported from Oxfordshire during 1981-1986. 5 The incidence rates for cerebral infarction and TIA lead to an estimation of the number of people in a defined population that may require diagnostic evaluation to characterize the mechanism of an ischemic event.…”
Section: Brown Et Al October 1998supporting
confidence: 59%
See 2 more Smart Citations
“…The percentage of carotid cases is considerably higher than that reported in Japan 8,14 but is similar to that reported in Oxfordshire. 5 The incidence of TMB in the present study is higher than that reported in a prospective study from Denmark, 16 but the frequency of TMB among all TIA cases (19%) is similar (17%) to that reported from Oxfordshire during 1981-1986. 5 The incidence rates for cerebral infarction and TIA lead to an estimation of the number of people in a defined population that may require diagnostic evaluation to characterize the mechanism of an ischemic event.…”
Section: Brown Et Al October 1998supporting
confidence: 59%
“…The incidence rates for Rochester used in prior comparisons were an underestimate of the true TIA incidence because of failure to detect some TIAs with the use of the medical record linkage system. 2,3,16 The present study, with ascertainment of cases simultaneously with stroke cases and with the use of a diagnosis index rubric that had been shown to detect additional cases that would have previously been missed, led to higher and more accurate incidence rates. Comparison of age-and sex-adjusted incidence rates with other sites from throughout the world (Table 4) shows much higher rates in Rochester.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The most well-recognized, but not the most common, etiology of TMB is carotid atherothromboembolism [1,2,3,4,5,6]. Therefore, transient ischemic attack should be considered in patients with TMB, and they should be managed promptly [1,2,3,4,5,6]. Although TMB is known to be attributed to ischemia and associated with many conditions, the pathogenesis of TMB remains obscure in up to 66% of these patients [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Table 4 indicates the crude incidence of TIAs reported from community based studies, which is reproduced from the paper of Dennis et al (22), and to which three other studies (21,23,24) couple of studies. Extracranial atherosclerosis has been reported to be less common in the Japanese than in white, leading us to the presumption that the incidence of TIAs is lower in the Japanese.…”
Section: Outline Of the Hisayama Studymentioning
confidence: 99%